Conflicting Priorities Between Risk Management and Treatment of Schizophrenia in Swiss Forensic Services—A Case Report - Steinau, Sarah; Brackmann, Nathalie; Sternemann, Ulf; Biller-Andorno, Nikola; Habermeyer, Elmar (Frontiers in Psychiatry, 2018)
Deprivation of liberty in Switzerland may be ordered within the context of the execution of measures. The Swiss Criminal Code provides measures focusing on the offender’s need for treatment. If an in-patient therapeutic measure in accordance with article 59 of the Swiss Criminal Code does not promise any relevant therapeutic success or if the offender is too high a risk for society, he may be sentenced to an indefinite incarceration according to article 64 of the Swiss Criminal Code. This constitutes a safety measure for dangerous offenders rather than a therapeutic treatment of the mental disorder itself. We will describe the case of a forensic-psychiatric patient who was ordered an indefinite imprisonment with only scarce psychiatric care for over fifteen years. Furthermore, we will put his course of treatment and the progress of his executional steps into context with ethical challenges in the forensic-mental health and correctional system.